Thetorah.com: a historical and contextual approach (Project TABS, 2017)
"Project TABS (Torah And Biblical Scholarship) is an educational organization founded to energize the Jewish people by integrating the study of the Torah and other Jewish texts with the disciplines and findings of academic scholarship."
Gesehen am 10.08.2017
Keywords: Website